1993
DOI: 10.1209/0295-5075/24/4/011
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism, Electronic Structure and Lattice Sites of Fe Ions Implanted into Yttrium

Abstract: Using perturbed γ-ray distribution techniques and in-beam Mössbauer spectroscopy, the magnetism, electronic structure, and lattice sites of Fe ions implanted into Y have been investigated. About 65% of the Fe atoms occupy interstitial sites, which come out to be non-magnetic. The remaining fractions is found on substitutional sites, and exhibits a nearly Curie-type susceptibility and Korringa-type spin dynamics. Local spin density calculations predict the magnetic moment, the hyperfine field and the isomer shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Not only that, later experiments by Riegel and Gross [4] and Kapoor et.al. [5]brought out some more intriguing results. It was found that iron impurities in Group V metals V, Nb, and Ta showed zero magnetic moments, whereas in Group VI metals Cr, Mo and W, there existed nonzero localized magnetic moments.…”
Section: Introductionmentioning
confidence: 99%
“…Not only that, later experiments by Riegel and Gross [4] and Kapoor et.al. [5]brought out some more intriguing results. It was found that iron impurities in Group V metals V, Nb, and Ta showed zero magnetic moments, whereas in Group VI metals Cr, Mo and W, there existed nonzero localized magnetic moments.…”
Section: Introductionmentioning
confidence: 99%